Property rights of the founder of Рrivate Еnterprise - Сурженко, Ольга Анатоліївна (Theory and practice of jurisprudence, 2019)
The article deals with the problems of legislative regulation of property rights of the founder (s) of a Private Enterprise in Ukraine. The modern legal regulation of relations concerning the founder's departure from a Private Enterprise and payment to him of the value of his property right are still far from perfect. This problem can be solved as follows. It is necessary to decide not so much with the very concept of a private enterprise, but with its existence in the legal field of Ukraine. Thus, the analysis of the property rights of the founder of a Private Enterprise proves that all these rights are similar to the rights of participants in business societies. This type of legal entities is not subject to proper legal regulation, which indicates that there is no need for separate regulation of a Private Enterprise as a legal entity, and that its common features with companies are so obvious that they do not need to separate a Private Enterprise from legal entities as another organizational entity. the legal form referred to in Art. 83 of the Civil Code of Ukraine. Therefore, if a Private Enterprise is not a special organizational and legal form of legal entities, then the property rights of its founders are similar to the property rights of members of the Limited Liability Company. If the charter of a Private Enterprise stipulates that it is not the owner of the property, then the property right of its founder is the property right. In such cases, the property relations between the Private Enterprise and its founder are similar to those between state or public utilities and their founders. It is proposed to repeal Art. 113 of the Economic Code of Ukraine and to provide in the Transitional Provisions of the Law of Ukraine “On Limited and Additional Liability Companies” that private enterprises are re-registered as limited liability companies with the provisions of this Law applied to their re-registration